2005
DOI: 10.1016/j.pt.2005.08.006
|View full text |Cite
|
Sign up to set email alerts
|

The Entamoeba histolytica genome: something old, something new, something borrowed and sex too?

Abstract: An ancient and potent pathogenEntamoeba histolytica is an intestinal protozoan parasite of humans that causes amebic colitis and amebic liver abscess: diseases associated with significant levels of morbidity and mortality worldwide [1]. The organism has a simple life cycle, existing as either the motile trophozoite or the infectious, hardy cyst form. Trophozoites of E. histolytica reside within the anaerobic confines of the human colon, lack mitochondria, derive energy from fermentation and reproduce by binary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 18 publications
(28 reference statements)
0
15
0
Order By: Relevance
“…Furthermore, despite their being no confirmed evidence of sex in Entamoeba , the sequenced genome reveals an almost complete complement of genes required for meiosis [42]. In light of this it is unclear why it is so difficult to achieve homologous recombination in this parasite.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, despite their being no confirmed evidence of sex in Entamoeba , the sequenced genome reveals an almost complete complement of genes required for meiosis [42]. In light of this it is unclear why it is so difficult to achieve homologous recombination in this parasite.…”
Section: Discussionmentioning
confidence: 99%
“…Population genetic studies of several parasite species have indicated that genetic exchange is likely to occur or has taken place evolutionarily recently in the species (see for example in T. vaginalis [18], Giardia [26] and other parasite species reviewed in [27]). In the enteric pathogen E. histolytica, analysis of the first reference genome revealed a complement of genes necessary for meiosis, pointing to the possibility of sex in natural populations [28]. However, more substantial evidence was not available until the generation of a large NGS dataset of ten lab-cultured lines from Mexico, Bangladesh, Italy, United Kingdom, Korea and Venezuela [29].…”
Section: Using Genome Sequence Data To Investigate Parasite Populatiomentioning
confidence: 99%
“…1975; Schuster 1976; Dacks and Roger 1999a; Goldstein 1999a; Ramesh et al. 2005; Stanley 2005). However, the exact mechanism of sexual developments in most of these lineages is obscure or deviant from those observed in animals, fungi and plants (Lahr et al.…”
Section: Introductionmentioning
confidence: 99%